Calvarial reconstruction using high-density porous polyethylene cranial hemispheres - Nitin J Mokal; Mahinoor F Desai (Indian Journal of Plastic Surgery)
Aims: Cranial vault reconstruction can be performed with a variety of autologous or alloplastic materials. We describe our experience using high-density porous polyethylene (HDPE) cranial hemisphere for cosmetic and functional restoration of skull defects. The porous nature of the implant allows soft tissue ingrowth, which decreases the incidence of infection. Hence, it can be used in proximity to paranasal sinuses and where previous alloplastic cranioplasties have failed due to implant infection. Materials and Methods: We used the HDPE implant in seven patients over a three-year period for reconstruction of moderate to large cranial defects. Two patients had composite defects, which required additional soft tissue in the form of free flap and tissue expansion. Results: In our series, decompressive craniectomy following trauma was the commonest aetiology and all defects were located in the fronto-parieto-temporal region. The defect size was 10 cm on average in the largest diameter. All patients had good post-operative cranial contour and we encountered no infections, implant exposure or implant migration. Conclusions: Our results indicate that the biocompatibility and flexibility of the HDPE cranial hemisphere implant make it an excellent alternative to existing methods of calvarial reconstruction.